OpenEMS – a free and open source equivalent‐circuit (EC) FDTD simulation platform supporting cylindrical coordinates suitable for the analysis of traveling wave MRI applications. (10th December 2012) - Liebig, Thorsten; Rennings, Andreas; Held, Sebastian; Erni, Daniel
SUMMARY: In this paper, we present a free and open source platform by using the equivalent‐circuit finite‐difference time‐domain (FDTD) method adapted to cylindrical coordinates to efficiently model cylindrically shaped objects. We will address the special characteristics of a cylindrical FDTD mesh such as the mesh singularity at r  = 0 and discuss how cylindrical subgrids for small radii can reduce the simulation time considerably. Furthermore, we will demonstrate the applicability and advantages of this cylindrical equivalent‐circuit FDTD method to evaluate new types of conformal ring antennas used in the context of high‐field (7T) traveling wave magnetic resonance imaging (MRI). Copyright © 2012 John Wiley & Sons, Ltd.